Pola Perilaku Harian Anak Rusa Timor (Rusa timorensis) di Penangkaran CV. Bahtera Satwa Desa Margorejo, Dawe Kudus: Pola Perilaku Harian Anak Rusa Timor (Rusa timorensis) - Febriani, Lili; Isdadiyanto, Sri; Kasiyati, Kasiyati (IPB University, 2025)
The phenomenon of the declining population of Timor deer (Rusa timorensis) has led the Indonesian government to designate them as a protected species. Captive breeding has become an effort to conserve Timor deer, and daily behavior serves as a measure of the success of the breeding program. The objective of this research was to evaluate the daily behavior patterns of Timor deer fawns, including movement, feeding, resting, social, alert, eliminative, and grooming behavior at the CV. Bahtera Satwa Breeding Center. Data collection for the research was conducted over 14 days using the scan sampling method. The results showed significant differences (p<0.05) in movement behavior, feeding, resting, social, and eliminative behavior between morning, afternoon, and evening. The frequency of social behavior in deer fawn was observed more often than in other behaviors, while the duration of resting activities was higher compared to other activities. The conclusion of this study was that the daily behavior patterns of Timor deer fawns, consisting of social and resting behaviors, were consistently performed in the morning and afternoon. The social behavior exhibited by the fawns was an effort to interact and explore their environment, while resting behavior was used to avoid heat and recover energy after morning activities.